Kelios mintys apie naująsias lenkų ir latvių literatūros istorijas - Jurgutienė, Aušra (Colloquia, 2024)
Being Poland: A New History of Polish Literature and Culture since 1918 (2018), ed. by Tamara Trojanowska, Joanna Nizynska and Przemysław Czapliński; with the assitance of Agnieszka Polakowska, Toronto Buffalo London: University of Toronto Press, 828 p. ISBN 978-1-4426-5018-3(cloth), ISBN 978-1-4875-2459-3 (paper). A New History of Latvian Literature: The Long Nineteenth Century, eds. Pauls Daija / Bendikts Kalnačs (2022) [Cross-Roads: Studies in Culture, Literary Theory, and History. Ed. by Ryszard Nycz, vol. 29], Peter Lang GmbH, 276 p. ISBN 978-3-631-86202-5 (Print), E-ISBN 978-3-631-85624-6, (E-PDF) E-ISBN 978-3-631-87395-3 (EPUB).